Factors Associated with the Incidence of Overweight in Junior High School Students - Pipit Tri Achmadi; Diyah Yulistika Handayani (UM Purwokerto Press, 2024)
Background: According to the 2018 Riskesdas data, 1 out of 7 Indonesian adolescents is overweight which leads to obesity. The obesity rate in children aged 5-12 years is also high, namely 9.2%, 13-15 years 4.8% and 16-18 years 4%. Obesity can be caused by several factors, including external factors (socioeconomic level, nutritional knowledge, culture) internal factors (consumption patterns, physical activity, psychological factors). Method: This study is an analytical observational type with a quantitative-qualitative research approach. The study sample consisted of 66 students selected using simple random sampling. Respondent data were collected through interviews using a semi-FFQ form for dietary habits and anthropometric measurements for nutritional status. Results: In this study, it was found that 31 (47%) had a fairly good diet and 35 (53%) students had a diet > 3 times a day. As many 44 (66.7%) students often do light physical activity, while 22 students (33.3%) with moderate activity 51 students (77.3%) have parents with more income and 15 (22.7%) students have sufficient pocket money A total of 36 and 30 (54.5% vs 45.5%) students respectively had good and bad nutrition knowledge. Conclusion: The occurrence of overweight among junior high school students is closely related to dietary patterns, nutritional knowledge, and weight status.